Prevalencija VKORC1 alela u populaciji Republike Srpske, Bosna i Hercegovina - Vidović, Vanja; Bećarević, Jelena; Radić Savić, Žana; Marić, Aljoša; Vidović, Stojko; Milovac, Irina; Maksimović, Nela (Scripta Medica, 2023)
Background/Aim: Warfarin is one of the most common orally prescribed anticoagulant in patients with deep venous thrombosis, myocardial or cerebral infarctions. The main side effects of non-adequate dose of these drugs are prolonged peripheral or internal bleeding. VKORC1 1173C>T polymorphism (rs9934438) is of particular importance, since carriers of non-wild type allele correlates with the lower dosage of warfarin therapy. Thus, the aim of the research was to determine the distribution of 1173C>T polymorphism in population of the Republic of Srpska, Bosnia and Herzegovina (RS) and to compare results with frequencies in other populations. Methods: A total of 124 healthy participants of both genders were enrolled in the study, from all parts of the RS. Molecular genotyping was performed by real-time PCR, using drug metabolism assays according to the manufacturer’s instructions. Results: Of the total number, 22 subjects (17.74 %) were genotyped as CC, 69 subjects (55.65 %) as CT and 33 subjects (26.61 %) as TT. The frequencies of alleles C and T were 45.18 % and 54.82 %, respectively. No statistical significance was found among allele distribution between genders (χ² = 0.236; p = 0.627). All observed genotype frequencies were in Hardy-Weinberg equilibrium. No statistical significance was observed among the frequency of minor T allele between presented findings and other European countries, besides Russia (p = 0.021). Conclusion: This was the first study analysing the distribution of rs9934438 alleles in population of the RS. These findings will be helpful in better and more precise drug prescribing in patients who require anticoagulant therapy.